Salmonella Typhi and Plasmodium falciparum Co-infection in a 12-year Old Girl with Haemoglobin E Trait from a Non-malarious Area in Bangladesh - Chowdhury, Fahmida; Chisti, Mohammod J; Khan, Ahmadul H; Chowdhury, Mohammad A; Pietroni, Mark AC (Journal of Health, Population and Nutrition, 2010)
A 12-year old girl from Uttar Badda, Dhaka, Bangladesh, was admitted to the Dhaka Hospital of ICDDR,B, with a 23-day history of fever and diarrhoea. After admission, she was treated for culture-proven Salmonella Typhi-associated infection and was discovered to be heterozygous for haemoglobin E. Despite treatment with appropriate antibiotics, the patient's condition did not improve, prompting further investigation, which revealed malaria due to Plasmodium falciparum. Dhaka is considered a malaria-free zone, and the patient denied recent travel outside Dhaka. Subsequently, the patient recovered fully on antimalarial therapy. Key words: Haemoglobin E; Malaria; Plasmodium falciparum; Salmonella Typhi; Typhoid; Bangladesh DOI: 10.3329/jhpn.v28i5.6162 J HEALTH POPUL NUTR 2010 Oct;28(5):529-531